K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\(9^x=27^4.81\)

\(\Rightarrow\left(3^2\right)^x=\left(3^3\right)^4.3^4\)

\(\Rightarrow3^{2x}=3^{12}.3^4\)

\(\Rightarrow3^{2x}=3^{16}\)

\(\Rightarrow2x=16\)

\(\Rightarrow x=8\)

Vậy \(x=8\)

11 tháng 7 2021

x = 27 4.  81

( 3=  ( 34. 34

2x = 312 . 34

2x  = 316

2 x = 16

   x = 8

23 tháng 9 2019

1, 27x.9x=927:81                                                        

   (33)x.(32)X=(32)27:34

   33X.32X=354:34

   33X+2X=350

     35X=350

Suy ra :5x=50

             x=10

    

12 tháng 3 2017

 Đặt A = (1/81)^x nhân 27^(2x) 
Đặt B = (-9)^4 
(1/81)^x = (1/9^2)^x = (1/9)^2x 
=> A = (1/9 nhân 27)^ 2x 
= 3^(2x) 
B: (-9)^4 = 9^4 = (3^2)^4 = 3^8 
A=B <=> 3^(2x) = 3^8 <=> 2x = 8 <=> x = 4

tk cho tớ nha

19 tháng 9 2016

a) \(\frac{x^7}{81}=27\)

=> x7 = 27.81

=> x7 = 33.34

=> x7 = 37

=> x = 3

Vậy x = 3

b) \(\frac{x^8}{9}=729\)

=> x8 = 729.9

=> x8 = 36.32

=> x8 = 38 = (-3)8

=> \(x\in\left\{3;-3\right\}\)

Vậy \(x\in\left\{3;-3\right\}\)

5 tháng 8 2016

x^7/81 = 27                                                    x^8/9 = 729

x^7 : 81= 27                                                   x^8  : 9 = 729

x^7       =27.81                                                x^8       = 729.9

x^7        =2187                                                x^8       =6561

x^7        = 3^7                                                  x^8       = 3^8

=> x      =3                                                       => x      = 3

5 tháng 8 2016

\(\frac{x^7}{81}=27\Rightarrow x^7=27.81=2187\Rightarrow x=\sqrt[7]{2187}=3\)

\(\frac{x^8}{9}=729\Rightarrow x^8=729.9=6561\Rightarrow x=\sqrt[8]{6561}=3\)

20 tháng 6 2019

Bài 2: 

a) \(\frac{x}{-27}=\frac{-3}{x}\Leftrightarrow-\frac{x}{27}=-\frac{3}{x}\Leftrightarrow-x.x=\left(-27\right).\left(-3\right)\Leftrightarrow-x^2=-81\Leftrightarrow\orbr{\begin{cases}x=9\\x=-9\end{cases}}\)

\(\Rightarrow\orbr{\begin{cases}x=9\\x=-9\end{cases}}\)

b) \(\frac{-9}{x}=\frac{-x}{\frac{4}{49}}\Leftrightarrow-\frac{9}{x}=-\frac{49x}{4}\Leftrightarrow-9.4=-x.49x\Leftrightarrow-36=-49x^2\Leftrightarrow\orbr{\begin{cases}x=\frac{6}{7}\\x=-\frac{6}{7}\end{cases}}\)

\(\Rightarrow\orbr{\begin{cases}x=\frac{6}{7}\\x=-\frac{6}{7}\end{cases}}\)

25 tháng 9 2016

\(\frac{x^7}{81}=27\Rightarrow x^7=27.81\Rightarrow x^7=3^3.3^4\Rightarrow x^7=3^7\Rightarrow x=3\)

\(\frac{x^8}{9}=729\Rightarrow x^8=729.9\Rightarrow x^8=3^6.3^2\Rightarrow x^8=3^8\Rightarrow x=3\)